(untitled) (Research, Society and Development, 2020)
This paper aims to investigate the nomenclatures given to vessels in the municipality of São João de Pirabas - Pará , the semantics of names and their colonial and decolonial influences. The article intends to discuss how social relations are established through the verification of these names, which may lead to the identification of references to the religiosity, ethnicity, knowledge and practices of the people of the fishing community surveyed. Ethnographic and qualitative research begins with field research to collect on-site subsidies through participatory forays into the “market port” where boats anchor in the city. The guiding conjecture of the research is that through the nomenclatures we can understand the colonial and decolonial influence that added to interculturality may have based the choice of boat names. Among the authors used are Weber (2004), Morin (2000), Dussel (2005) Maués (2010) and Prandi (2020). As a result, it was obtained the perception that in that city there is a significant number of boats named according to their owners’ religiosity, divided between Catholicism and Protestantism, as well as the socioeconomic leveling of these categories. It was found that the symbolism present in such names explains the relations established between fishermen and vessel owners about the terminology of the boats, as well as the colonial and decolonial aspects relevant to the vessel’s naming action.